Recent progress in separation prediction of counter‐current chromatography. Issue 1 (19th October 2020) - Guo, Yuru; Tong, Shengqiang; Zhang, Keqing; Yan, Jizhong
Abstract: As a liquid‐liquid partition chromatography, counter‐current chromatography has advantages in large sample loading capacity without irreversible adsorption, which has been widely applied in separation and purification fields. The main factors, including partition coefficient, two‐phase solvent systems, apparatus, and operating parameters greatly affect the separation process of counter‐current chromatography. To promote the applications of counter‐current chromatography, it is essential to develop theoretical research to master the principles of counter‐current chromatographic separations so as to achieve predictions before laborious trials. In this article, recent progress about separation prediction methods are reviewed from a point of the steady and unsteady state of the mass transfer process of counter‐current chromatography and its mass transfer characteristics, and then it is divided into three aspects: prediction of partition coefficient, modeling the thermodynamic process of counter‐current chromatography, and modeling the dynamic process of counter‐current chromatography.